Acute Kidney Injury and Abnormalities on Brain Magnetic Resonance Imaging or Death in Infants with Hypoxic–Ischemic Encephalopathy: A Case–Control Study - DeSantis, Eliza; Talekar, Kiran; Dougherty, Margaret; Carola, David; Solarin, Kolawole; McElwee, Dorothy; Adeniyi-Jones, Susan; Aghai, Zubair H. (American Journal of Perinatology, 2023)
Objective This study aimed to analyze the association between acute kidney injury (AKI) and abnormalities on brain magnetic resonance imaging (MRI) or death in neonates treated with therapeutic hypothermia for hypoxic-ischemic encephalopathy (HIE).Study Design This is a retrospective case–control analysis of 380 neonates born at ≥35 weeks' gestation treated with therapeutic hypothermia for HIE. Death or abnormal brain MRI using the basal ganglia watershed scoring system was compared between neonates with and without AKI.Results A total of 51 (13.4%) neonates had AKI. Infants with AKI had higher rates of the composite of death or abnormal brain MRI (74.5 vs. 38.3%; p < 0.001). Rate of death (21.6 vs. 5.5%; p < 0.001) and severe abnormalities on MRI or death (43.1 vs. 19.1%; p < 0.001) were also higher in neonates with AKI.Conclusion AKI is strongly associated with abnormalities on brain MRI or death in neonates with HIE. Identification of AKI in this patient population may be helpful in guiding clinical management and predicting potential neurodevelopmental impairment.Key Points
Keywords: acute kidney injury; hypoxic-ischemic encephalopathy; neonate; hypothermia